2012
DOI: 10.1016/j.juro.2012.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Seminal Clusterin Gene Expression Associated with Seminal Variables in Fertile and Infertile Men

Abstract: CLU gene expression was significantly increased in the semen samples of infertile men. It correlated negatively with sperm count, motility, acrosin activity, linearity index and linear velocity, and positively with the percent of sperm abnormal forms and DNA fragmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 28 publications
(19 reference statements)
3
26
0
Order By: Relevance
“…Even when compared with clusterin expression in the reproductive fluids of other species, we have studied using the same 2D SDS-PAGE approach, such as the bovine (Moura et al 2007(Moura et al , 2010, ovine , and domestic swine (S. scrofa; V R Cadavid, However, the precise functional meaning of such event is unclear. Clusterin is multifunctional, acting as a chaperone (Humphreys et al 1999), protecting reproductive tract cells against apoptosis (Bailey et al 2002) or complement attack (Meri & Jarva 2001), and assisting with removal of damaged sperm in the epididymis of men (Zalata et al 2012). The chaperone activity of clusterin is consistent with its propensity to interact with different proteins in vivo (Carver et al 2003) and in acoordance with the network analysis we presently show.…”
Section: Proteins Associated With Protection Of Sperm Integrity and Fsupporting
confidence: 79%
“…Even when compared with clusterin expression in the reproductive fluids of other species, we have studied using the same 2D SDS-PAGE approach, such as the bovine (Moura et al 2007(Moura et al , 2010, ovine , and domestic swine (S. scrofa; V R Cadavid, However, the precise functional meaning of such event is unclear. Clusterin is multifunctional, acting as a chaperone (Humphreys et al 1999), protecting reproductive tract cells against apoptosis (Bailey et al 2002) or complement attack (Meri & Jarva 2001), and assisting with removal of damaged sperm in the epididymis of men (Zalata et al 2012). The chaperone activity of clusterin is consistent with its propensity to interact with different proteins in vivo (Carver et al 2003) and in acoordance with the network analysis we presently show.…”
Section: Proteins Associated With Protection Of Sperm Integrity and Fsupporting
confidence: 79%
“…In the current study, it was found that sCLU negatively correlates with sperm morphology, protamine deficiency, and DNA fragmentation since less sCLU was detected in the seminal plasma of infertile patients. Although extensive research has been previously done on the relationship between CMA 3 -positivity, DNA damage, seminal CLU gene expression, and infertility (Zini et al, 2001;Nasr-Esfahani et al, 2004Muciaccia et al, 2012;Zalata et al, 2012), to our knowledge this is the first report on the correlation between sCLU of seminal plasma, sperm parameters, protamine deficiency, and DNA fragmentation in humans.…”
Section: Discussionmentioning
confidence: 93%
“…Clusterin (CLU), a heterodimeric, disulfide-linked glycoprotein, has been suggested as an alternate marker for seminal oxidative stress (40). It is interesting that, as with the other HSPs described previously, CLU was found at higher protein levels in sperm that resulted in poor blastocyst development.…”
Section: Figurementioning
confidence: 87%
“…1). Others have reported that CLU exerts a small heat-shock-protein-like stress-induced chaperone activity and is an extremely sensitive cellular biosensor to environmental and/or oxidative stress (40,41). The conventional CLU is expressed in a wide variety of tissues and cells and has been linked to several biologic processes, including aging, tumorigenesis, neurodegeneration, and cardiovascular and metabolic syndromes (41).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation